Penerapan Metode Rapid Application Development Dalam Membangun Website E-Commerce - Gushelmi , Gushelmi (Jurnal Sains dan Teknologi (JSIT), 2022)
Information technology has been used by all aspects of life and has become an inseparable part of all community activities, especially in the business world. Currently, marketing and product promotion activities are still using banners and social media and reporting activities are still being done manually. This causes a waste of promotional costs and the accuracy of the report data may not be in line with changes in existing data. For this reason, an electronic sales information system (E-Commerce) was designed using the Rapid Application Development (RAD) method using the PHP programming language and MYSQL database. The program designed will produce an E-Commerce sales system that will help the sales system run, as well as a clear bookkeeping report to the leadership. With this new system, it is hoped that there will be changes in sales governance and reporting for the better.